Neuroimmune crosstalk in chronic neuroinflammation: microglial interactions and immune modulation - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Cellular Neuroscience, 2025)
Neuroinflammation is a fundamental feature of many chronic neurodegenerative diseases, where it contributes to disease onset, progression, and severity. This persistent inflammatory state arises from the activation of innate and adaptive immune responses within the central nervous system (CNS), orchestrated by a complex interplay of resident immune cells, infiltrating peripheral immune cells, and an array of molecular mediators such as cytokines, chemokines, and extracellular vesicles. Among CNS-resident cells, microglia play a central role, exhibiting a dynamic spectrum of phenotypes ranging from neuroprotective to neurotoxic. In chronic neurodegenerative diseases, sustained microglial activation often leads to the amplification of inflammatory cascades, reinforcing a pathogenic cycle of immune-mediated damage. Intercellular communication within the inflamed CNS is central to the persistence and progression of neuroinflammation. Microglia engage in extensive crosstalk with astrocytes, neurons, oligodendrocytes, and infiltrating immune cells, shaping both local and systemic inflammatory responses. These interactions influence key processes such as synaptic pruning, phagocytosis, blood–brain barrier integrity, and cytokine-mediated signaling. Understanding the mechanisms of cell–cell signaling in this context is critical for identifying therapeutic strategies to modulate the immune response and restore homeostasis. This review explores the key players in CNS neuroinflammation, with a focus on the role of microglia, the molecular pathways underlying intercellular communication, and potential therapeutic approaches to mitigate neuroinflammatory damage in chronic neurodegenerative diseases.